Sweat lactate response during cycling at 30 degrees C and 18 degrees C WBGT - Green, J. M.; Pritchett, R. C.; Tucker, D. C.; Crews, T. R.; McLester, J. R. (Journal of Sports Sciences, 2004)
Sweat lactate reflects eccrine gland metabolism. However, the metabolic tendencies of eccrine glands in a hot versus thermoneutral environment are not well understood. Sixteen male volunteers completed a maximal cycling trial and two 60-min cycling trials [30 degrees C = 30 +/- 1 degrees C and 18 degrees C = 18 +/- 1 degrees C wet bulb globe temperature (WBGT)]. The participants were requested to maintain a cadence of 60 rev min(-1) with the intensity individualized at approximately 90% of the ventilatory threshold. Sweat samples at 10, 20, 30, 40, 50 and 60 min were analysed for lactate concentration. Sweat rate at 30 degrees C (1380 +/- 325 ml x h(-1)) was significantly greater (P < 0.05) than at 18 degrees C (632 +/- 311 ml x h(-1)). Sweat lactate concentration was significantly greater (P < 0.05) at each time point during the 18 degrees C trial, with values between trials tending to converge across time. During the 30 degrees C trial, both heart rate (20, 30, 40, 50 and 60 min) and rectal temperature (30, 40, 50 and 60 min) were significantly higher than in the 18 degrees C trial. Higher sweat lactate concentrations coupled with lower sweat rates may indicate a greater relative contribution of oxygen-independent metabolism within eccrine glands during exercise at 18 degrees C. Decreases in sweat lactate concentration across time suggest either greater dilution due to greater sweat volume or increased reliance on aerobic metabolism within eccrine glands. The convergence of lactate concentrations between trials may indicate that time-dependent modifications in sweat gland metabolism occur at different rates contingent partially on environmental conditions.